Maternal cognitive function during pregnancy in relation to hypo‐ and hyperthyroxinemia. (6th November 2019) - Pop, Victor J.; Ormindean, Vlad; Mocan, Andreia; Meems, Margreet; Broeren, Maarten; Denollet, Johan K.; Wiersinga, Wilmar M.; Bunevicius, Adomas
Abstract: Objective: To assess a possible relationship between maternal cognitive dysfunction during pregnancy and hypothyroxinemia, adjusted for major confounders. Background: Thyroid dysfunction in general is associated with cognitive dysfunction. Cognitive dysfunction is common during pregnancy. Design: Prospective follow‐up study from 12 to 32 weeks of pregnancy. Participants: 2082 healthy pregnant women. Measurements: Cognitive function, depression and sleeping problems were assessed by self‐report questionnaires at 12, 22 and 32 weeks of gestation, higher scores reflecting more symptoms. FT4, TSH and TPO‐Ab were assessed at 12 weeks of gestation. Definitions: healthy (euthyroxinemia) control group: FT4 within 10‐90th percentiles, without elevated TPO‐Ab titres and TSH within first trimester‐specific reference range (0.23‐4.0 mU/L). Hypothyroxinemia: FT4 <2.5th percentile with TSH within first trimester‐specific reference range. Poor cognitive function: a score >1 SD > mean on the cognitive function scale. Results: A total of 54 women showed hypothyroxinemia and 1476 women had euthyroxinemia. At 12 weeks, multiple logistic regression showed that poor cognitive function was independently related to hypothyroxinemia: OR: 2.9 (95% CI: 1.6‐5.4), adjusted for depression (OR: 3.1; 95% CI: 2.7‐4.6) and sleeping problems (OR: 2.8, 95% CI: 1.9‐3.9). TPO‐Ab + women with hypothyroxinemia had the highest levels of cognitive dysfunction. Other cut‐offs of hypothyroxinemia (<5th or <10th percentile with normal TSH) showed similar results. GLM‐ANOVA showed that throughout pregnancy women with hypothyroxinemia at 12 weeks had significantly higher cognitive dysfunction scores compared with the healthy controls: F  = 12.1, P  = .001. Conclusions: Women with hypothyroxinemia during early gestation are at risk for poor cognitive function throughout gestation, adjusted for depression and sleeping problems.